Government ideology in donor and recipient countries: does ideological proximity matter for the effectiveness of aid? - Dreher, Axel; Minasyan, Anna; Nunnenkamp, Peter (European economic review, 2015)
Political misalignment and greater ideological distance between donor and recipient governments may render foreign aid less effective by adding to transaction costs and eroding trust. We test this hypothesis empirically by considering the political ideology of both governments along the left-right spectrum in augmented models on the economic growth effects of aid. Following the estimation approach of Clemens et al. (2012), we find that aid tends to be less effective when political ideology differs between the donor and the recipient.